Writing a proposal for your dissertation guidelines and examples - Terrell, Steven R. (New York The Guilford Press, 2016)
"This user-friendly guide helps students get started on--and complete--a successful doctoral dissertation proposal by accessibly explaining the process and breaking it down into manageable steps. Steven R. Terrell demonstrates how to write each chapter of the proposal, including the problem statement, purpose statement, and research questions and hypotheses; literature review; and detailed plan for data collection and analysis. Of special utility, end-of-chapter exercises serve as building blocks for developing a full draft of an original proposal. Numerous case study examples are drawn from across the social, behavioral, and health science disciplines. Appendices present an exemplary proposal written three ways to encompass quantitative, qualitative, and mixed-methods designs. Pedagogical Features: *"Let's Start Writing" exercises leading up to a complete proposal draft. *"Do You Understand" checklists of key terms plus an end-of-book glossary. *End-of-chapter quizzes with answers. *Case study examples from education, psychology, health sciences, business, and information systems. *Sample proposal with three variants of the methods chapter: quantitative, qualitative, and mixed methods"-- Provided by publisher.
Machine generated contents note: 1. Developing the Problem Statement for Your Dissertation Proposal -- Introduction -- The Doctoral Experience -- The Problem Is the Problem -- Finding a Good Research Problem -- Characteristics of a Good Problem -- Writing the Problem Statement -- The Problem Statement as Part of a Dissertation Proposal -- Summary of Chapter One -- Do You Understand These Key Words and Phrases? -- Let's Start Writing Our Own Proposal -- 2. Writing Purpose Statements, Research Questions, and Hypotheses -- Introduction -- The Quantitative Purpose Statement -- Purpose Statements for Qualitative Studies -- Defining and Describing a Research Question -- The Methodological Point of Departure -- Research Questions Will Ultimately Lead to the Study's Research Method -- Getting Back to Stating Our Research Question -- A Word of Caution! -- Putting It Together: Problem Statements, Purpose Statements, and Research Questions -- Problem Statements, Purpose Statements, and Research Questions in the Literature -- Stating Hypotheses for Your Research Study -- An Example of Stating Our Hypotheses -- Understanding the Four Basic Rules for Hypotheses -- The Direction of Hypotheses -- Hypotheses Must Be Testable via the Collection and Analysis of Data -- Research versus Null Hypotheses -- All Hypotheses Must Include the Word "Significant" -- Other Parts of Chapter 1 of the Dissertation -- Summary of Chapter Two -- Do You Understand These Key Words and Phrases? -- Review Questions -- Progress Check for Chapter 1 of the Dissertation Proposal: The Introduction -- Let's Continue Writing Our Own Dissertation Proposal -- 3. Writing the Review of Literature for Your Study -- Introduction -- What Is a Review of Literature and What Is Its Purpose? -- There Isn't a Magic Formula for Writing a Review of Literature -- Phase 1. Getting Ready to Write a Review of Literature -- Phase 2. Writing the Review of Literature -- Summary of Chapter Three -- Do You Understand These Key Words and Phrases? -- Review Questions -- Progress Check for Chapter 3 of the Dissertation Proposal: The Review of Literature -- Let's Continue Writing Our Own Dissertation Proposal -- 4. The First Part of Your Dissertation Research Method -- Introduction -- Philosophy 101 -- The Research Paradigm -- Nonrandom (Nonprobabalistic) Sampling -- Identifying the Population and a Sample for Your Study -- Summary of the Sampling Process -- Data Collection Instruments -- Instruments for Quantitative Research -- Instruments for Qualitative Research -- Reliability and Validity -- Plans for Data Analysis -- Ethical Considerations -- Plans for Presenting the Results -- Summary of Your Proposal -- Summary of Chapter Four: The First Part of Your Dissertation Research Method -- Do You Understand These Key Words and Phrases? -- Review Questions -- 5. Quantitative Research Methods -- Introduction -- Different Types of Data -- Quantitative Research Designs -- Survey Research -- Correlational Research -- Causal-Comparative Research -- Hypothesis Testing -- Experimental Research -- The Validity of Your Study -- Threats to the Internal Validity of Your Study -- Threats to the External Validity of Your Study -- Experimental Research Designs -- Preexperimental Designs -- Quasi-Experimental Designs -- Experimental Designs -- Putting This All Together for the Quantitative Dissertation Proposal -- Chapter 3 of a Quantitative Dissertation Proposal -- Our First Example of Chapter 3 of a Proposal -- Summary of Chapter Five -- Do You Understand These Key Words and Phrases? -- Review Questions -- Progress Check for Chapter 3 of a Quantitative Dissertation Proposal -- Let's Continue Writing Our Own Dissertation Proposal -- Appendix 5.1. Example of a Descriptive Research Study -- Appendix 5.2. Example of a Correlational Research Study -- Appendix 5.3. Example of a Quasi-Experimental Research Study -- Appendix 5.4. Example of an Experimental Research Study -- Appendix 5.5. Threats to the Validity of an Experimental Study -- 6. Qualitative Research Methods -- Introduction -- An Overview of Qualitative Methodologies -- The Role of the Researcher -- The Format of a Qualitative Dissertation Proposal -- Chapter 1 of a Qualitative Dissertation Proposal: The Introduction -- Chapter 3 of a Qualitative Dissertation Proposal: Research Methods -- Choosing the Right Qualitative Research Method -- Participants and Sampling -- Instruments -- Research Procedures -- Plans for Data Analysis -- The Validity and Reliability of a Qualitative Study -- Ethical Considerations -- Plans for Presenting the Results -- Summary -- Summary of Chapter Six -- Do You Understand These Key Words and Phrases? -- Review Questions -- Progress Check for Chapter 3 of a Qualitative Dissertation Proposal -- Let's Continue Writing Our Own Dissertation Proposal -- Appendix 6.1. Narrative Study Procedures: The Case of the Unfortunate Departure -- Appendix 6.2. Phenomenological Study Procedures: The Case of Sending Your Child to Safety -- Appendix 6.3. Ethnographic Study Procedures: The Case of Climbing the Mountain -- Appendix 6.4. Case Study Procedures: The Case of the Standardized Test -- Appendix 6.5. Grounded Theory Procedures: The Case of Homelessness -- Appendix 6.6. Content Analysis Procedures: The Case of the Eye Witness -- 7. Mixed Methods Research Designs -- Introduction -- An Overview of Mixed Methods Research -- The Format of a Mixed Methods Proposal -- Chapter 1 of a Mixed Methods Study: The Introduction -- Background, Statement of the Problem, and Significance of the Study -- The Central Purpose of the Study -- Research Questions -- Hypotheses for Mixed Methods Studies -- Chapter 2 of a Mixed Methods Dissertation Proposal: The Review of Literature -- Chapter 3 of a Mixed Methods Dissertation Proposal: Research Methods -- The Mixed Methods Paradigm -- Research Design -- The Three Major Mixed Methods Designs -- Participants and Sampling -- Instruments -- Research Procedures -- Plans for Data Analysis -- Ethical Considerations -- Plans for Presenting the Results -- Summary of Chapter Seven -- Do You Understand These Key Words and Phrases? -- Review Questions -- Progress Check for Chapter 3 of a Mixed Methods Dissertation Proposal: The Research Methods -- Appendix 7.1. Sequential Explanatory Design: The Case of the Tutors -- Appendix 7.2. Sequential Exploratory Design: The Case of the Academies -- Appendix 7.3. Convergent Design: The Case of Calling It In -- Epilogue: Have We Accomplished What We Set Out to Do? -- Appendix A. Progress Check for Chapter 1 of a Dissertation Proposal: The Introduction -- Appendix B. Progress Check for Chapter 2 of a Dissertation Proposal: The Review of Literature -- Appendix C. Progress Check for Chapter 3 of a Quantitative Dissertation Proposal -- Appendix D. Progress Check for Chapter 3 of a Qualitative Dissertation Proposal -- Appendix E. Progress Check for Chapter 3 of a Mixed Methods Dissertation Proposal -- Answers to Review Questions -- Glossary -- References -- Index -- About the Author.
Includes bibliographical references and index.
Keywords: Dissertations, Academic -- Handbooks, manuals, etc; Proposal writing in research -- Handbooks, manuals, etc